2011
DOI: 10.1111/j.1540-6288.2010.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Chinese Stock Market Cycles Duration Independent?

Abstract: This paper studies the duration properties of the Chinese stock market cycle. We find evidence for duration dependence in both A-share and B-share markets for whole cycles. The results reject the random-walk hypotheses for both markets. For half cycles, evidence of duration dependence for expansions in the Shanghai A-share market is found. For the Shenzhen B-share market, there is little evidence of duration dependence for half cycles. Although the Bshare market is less liquid as compared to the A-share market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
4
4
0
Order By: Relevance
“…This has been indicated by p 1,1 < p 2,2 . This result is consistent with those stated by Girardin and Liu (2003) and Chen et al (2011) in which they find that the mean duration of the contraction period is greater than the expansion period for the Chinese market.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This has been indicated by p 1,1 < p 2,2 . This result is consistent with those stated by Girardin and Liu (2003) and Chen et al (2011) in which they find that the mean duration of the contraction period is greater than the expansion period for the Chinese market.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, the absolute values of the mean returns in bull markets are higher than the bear markets. The mean return for the A-index is higher than the mean return for the B-index in both Shanghai and Shenzhen markets. This result is comparable to those mentioned by Chen et al (2011) and Yan et al (2007) in which they found that the difference of return between the bull and bear markets could be more than double and highly significant compared to those of traditional markets (Schaller and Van Norden, 2002; and Gonzalez et al , 2005). Most of the mean returns are significant. The mean return of the A-index is equal to the mean return of composite index.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations